1995
DOI: 10.1056/nejm199504203321602
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Dysplastic and Malignant Lip Lesions in Renal-Transplant Recipients

Abstract: Renal-transplant recipients have an increased prevalence of leukoplakia, dysplasia, and cancer of the lip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(68 citation statements)
references
References 17 publications
1
65
1
1
Order By: Relevance
“…Further studies are needed to seek the definitive characterisation of the risk factors detected, as well as the identification of other factors that are probably involved. In this sense, the present study suggests a possible hypothesis for future verification: the finding of an association with warts and clinical antecedents in any part of the body suggests the possible implication of variables related to viral components and/or immunosuppression (Dinehart et al, 1990;King et al, 1995). Finally, the risk associated with high alcohol intake may be related, at least in part, to certain nutritional deficits not explored by this study (Franceschi et al, 1991).…”
Section: Discussionmentioning
confidence: 52%
“…Further studies are needed to seek the definitive characterisation of the risk factors detected, as well as the identification of other factors that are probably involved. In this sense, the present study suggests a possible hypothesis for future verification: the finding of an association with warts and clinical antecedents in any part of the body suggests the possible implication of variables related to viral components and/or immunosuppression (Dinehart et al, 1990;King et al, 1995). Finally, the risk associated with high alcohol intake may be related, at least in part, to certain nutritional deficits not explored by this study (Franceschi et al, 1991).…”
Section: Discussionmentioning
confidence: 52%
“…The occurrence of lip cancer among patients with naturally and medically induced immunosuppression suggests that the high rates among farmers may be due to factors that affect the immune system (47). There may be factors in the agricultural environment that induce immune system deficiencies (40).…”
Section: Discussionmentioning
confidence: 99%
“…An increased frequency of lesions with epithelial dysplasia of the lips (but not oral mucosa) has been observed in some but not all iatrogenically immunosuppressed patients (King et al, 1995;Seymour et al, 1997).…”
Section: (G) Leukoplakiamentioning
confidence: 99%
“…There is an increased prevalence of dysplastic and malignant lip lesions in immunosuppressed renal-transplant recipients (King et al, 1995) and liver transplant recipients (Haagsma et al, 2001). Oral leukoplakia has progressed rapidly to squamous cell carcinoma in some immunosuppressed patients (Hernandez et al, 2003), and oral squamous cell carcinoma has been reported in immunosuppressed patients without any recorded precursor lesion (Varga and Tyldesley, 1991).…”
Section: (E) Drug-related Neoplasms and Potentially Malignant Lesionsmentioning
confidence: 99%